ETIKA PROFESI DALAM BIDANG HUKUM DI ERA DIGITAL: ANTARA SIKAP DAN PERUBAHAN SOSIAL - Muhamad. Fikri Andriyana; Muhammad Hapid Khoironi; Firdaussiah Firdaussiah; Ainun Salsabila (Kampus Akademik Publiser, 2024)
Professional ethics in the legal field are becoming increasingly relevant and significant in this digital era. As a rule of appropriate behavior in the workplace, a code of ethics is very important to maintain the honor of the profession and protect society from abuse of power and justice in the legal field. Professional ethics in the legal field is centered on readiness to provide services that are altruistic and focused on the good of society.To be relevant and effective in defending the interests of society in facing social changes caused by the digital era, the ability to adapt and revolution is needed. The aim of this research is to determine professional ethical attitudes towards social change in the digital era, especially in the legal field. The author of this research used library research methodology, taking sources from books and journals. In this way, researchers can draw conclusions about the urgent need for attitudes and changes in society regarding professional ethics in the legal field, because social developments in the digital era have an impact on professional behavior patterns in carrying out their professional mandates and highlight the need for more concrete ethics. In order for a professional to act professionally, an investigation into professional ethics is also required as part of this.